Effects of dual bio-fuel (Jatropha biodiesel and turpentine oil) on a single cylinder naturally aspirated diesel engine without EGR. (25th March 2017) - Dubey, Pankaj; Gupta, Rajesh
Highlights: The concept of dual bio-fuel blends is adopted to eliminate the use of diesel in a diesel engine. Low viscous turpentine oil and high viscous Jatropha methyl ester were used as renewable bio-fuel. NOx, HC, CO and smoke emission for BT50 were reduced by 4.72%, 4.56%, 42.5% and 29.16% than diesel. Dual fuel blend is found to be a good substitute to diesel fuel in performance and emissions. Abstract: The significance of this present investigation undertakes the feasibility study of a new combination of bio-fuels. For this rationale; the diesel engine operated with blends of Jatropha biodiesel and turpentine oil with a view to completely eliminate dependency on fossil fuel. Jatropha biodiesel (methyl ester) and turpentine oil is a high and low viscosity fuels combination with comparable heating values to that of diesel; this makes conducive for its use in a diesel engine. Extensive experimental work is carried out on a Kirloskar make the single cylinder, natural aspired diesel engine to examine combustion performance and emission characteristics using Jatropha methyl ester with turpentine oil blends (dual fuel blends) and conventional diesel. Dual fuel blends are found to be the best substitute to conventional diesel fuel in all aspects such as performance and emissions. Further, BT 50 resulted at full load condition, reduction of 2.9%, 4.72%, 4.56%, 42.5% and 29.16% in the brake thermal efficiency, NOx, HC, CO and smoke respectively while CO2 emissions increase 10.7%.